SCIENTIFIC APPROACH TO CONSIDERING PROPERTIES IN THE DESIGN OF GARMENTS MADE FROM KNITTED FABRICS - Rahmatova, Sadoqat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In the design of knitted garments, twisting (torsion)—a tendency of the fabric edges to curl or distort—is considered one of the most important physical-mechanical properties. This phenomenon arises from the structural characteristics of knitted fabrics, yarn interlooping, yarn tension, and elasticity, and is particularly visible in thin, highly elastic, direction-sensitive knits. Excessive twisting results in deformation of garment shape and negatively affects fitting and appearance. This article analyzes scientifically-based approaches to reducing the twisting property during the engineering and design of knitted products.